2019
DOI: 10.3389/fchem.2019.00084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface and Bulk Properties of Mesoporous Carbons on the Electrochemical Behavior of GOx-Nanocomposites

Abstract: Biofuel cell (BFC) electrodes are typically manufactured by combining enzymes that act as catalysts with conductive carbon nanomaterials in a form of enzyme-nanocomposite. However, a little attention has been paid to effects of the carbon nanomaterials' structural properties on the electrochemical performances of the enzyme-nanocomposites. This work aims at studying the effects of surface and bulk properties of carbon nanomaterials with different degrees of graphitization on the electrochemical performances of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…In this work, we confirmed that the SPSC had a power density of 0.62 mW/cm 2 through glucose sensing of 11 mM glucose concentration. Studies related to glucose-based BFCs with glucose oxidase enzyme reported a lower power density as tens of μW/cm 2 in a solution similar to or higher than the glucose concentration used in this work. , Compared to the result of the recently reported high-performance BFC study that showed 3.7 mW/cm 2 power density in a 300 mM glucose solution, we verified that high power was generated by charging the supercapacitor by glucose oxidation reactions in this study. We further showed that Arduino can be used to distinguish between normal, prediabetes, and diabetes.…”
Section: Introductionsupporting
confidence: 84%
“…In this work, we confirmed that the SPSC had a power density of 0.62 mW/cm 2 through glucose sensing of 11 mM glucose concentration. Studies related to glucose-based BFCs with glucose oxidase enzyme reported a lower power density as tens of μW/cm 2 in a solution similar to or higher than the glucose concentration used in this work. , Compared to the result of the recently reported high-performance BFC study that showed 3.7 mW/cm 2 power density in a 300 mM glucose solution, we verified that high power was generated by charging the supercapacitor by glucose oxidation reactions in this study. We further showed that Arduino can be used to distinguish between normal, prediabetes, and diabetes.…”
Section: Introductionsupporting
confidence: 84%
“…The reason is traced to the transmembrane flux of water/ions, as confirmed by the water layer test (Figure 3). Although MCB is hydrophobic in nature [22], there may still be local island or point contacts between the membrane and the conducting substrate, which act as pathways for water. This is supported by the impedance study that indicated fusion between MCB and membrane.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we report multiplexed SCISEs based on PCB with mesoporous carbon black (MCB) for transduction. MCB belongs to a special group of conductive carbon blacks, and is characterized by high surface area (150-250 m 2 /g) [21], high hydrophobicity, and possesses low amount of surface functional groups [22]. It has significantly improved stability of ISEs based on capillary tubes compared to coated wire electrode [23].…”
Section: Introductionmentioning
confidence: 99%